1990
DOI: 10.2134/jeq1990.00472425001900030035x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Napropamide on Clay and Soil in the Presence of Dissolved Organic Matter

Abstract: Dissolved organic matter (DOM) can affect the distribution of solutes between solution and sorbed phases and the availability and environmental fate of the solutes. Batch sorption isotherm techniques were used to evaluate solute-solute and solute-sorbent interactions that control the effects of DOM on the sorption of a nonionic, moderately polar organic solute by solid sorbents. The sorption of napropamide (2-(a-naphthoxy-7V,A'-diethyl propionamide) by NaS Cu 2 *-, and Al^-montmorillonite decreased when dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 0 publications
4
27
1
2
Order By: Relevance
“…The association of DOM with NOCs such as nonionic pesticides in solution phase is well documented, and has been proposed as an important process that results in solubility enhancement and reduced the sorption of these compounds by soil sorbents [13,14,17,24,25]. There is also much evidence of the interaction of DOM with PAHs in aqueous solution.…”
Section: Effect Of Inherent Dom On Phenanthrene Sorption By Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of DOM with NOCs such as nonionic pesticides in solution phase is well documented, and has been proposed as an important process that results in solubility enhancement and reduced the sorption of these compounds by soil sorbents [13,14,17,24,25]. There is also much evidence of the interaction of DOM with PAHs in aqueous solution.…”
Section: Effect Of Inherent Dom On Phenanthrene Sorption By Soilsmentioning
confidence: 99%
“…Some studies revealed that the presence of DOM promoted sorption of NOCs such as nonionic pesticides [21,24]. By contrast, in other cases the sorption of NOCs was obviously inhibited in the presence of DOM [4,5,17,25]. Cox et al [18] reported that DOM reduced sorption of herbicide due to DOM-herbicide interactions and/or competition for sorption sites on soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by interactions between the soil and the organic matter of LSS that could result in some blockage of sorption sites for atrazine on both soil and LSS. Moreover, the presence of DOM fi'om LSS (LSSDOM) could also reduce atrazine sorption on soil through stable interactions in solution or by processes taking place at the soil/solution interface, such as competition for sorption sites on the soil surface [13,23]. In fact, DOC measured in the supematant of the soil-LSS mixtures before atrazine addition (Table 1) were only 25-50% of the initially added DOC, indicating that much of the LSSDOM is sorbed by the soil.…”
Section: Sorption Ofatrazine On Lss-amended Soilmentioning
confidence: 99%
“…3 between the experimental and calculated Kf values for the soil-LSS mixtures. The association of DOM with organic compounds in the solution phase has been proposed as the principal process which can reduce the sorption of organic compounds by solid sorbents [23][24][25];…”
Section: Effect Of Lssdom On Atrazine Sorption By Soilmentioning
confidence: 99%
See 1 more Smart Citation